Use of GLP-1 Analogues in Patients with Schizophrenia and Other Neuropsychiatric Disorders: A Literature Review - Pernal, Maja; Roguska, Zofia; Poniewozik, Paweł; Grabowski, Krzysztof; Dziuba, Natalia; Sim, Aleksandra; Mioduszewska, Joanna; Rot, Paweł; Poniewozik, Piotr; Zuzak, Andrzej (Quality in Sport, 2026)
Background: Schizophrenia is a chronic mental disorder associated with an increased risk of metabolic disturbances such as obesity, insulin resistance, and type 2 diabetes, as well as cognitive impairment. This is due to both the pathophysiology of the disease and the use of second-generation antipsychotics. Aim of the study: To review the literature on the use of GLP-1 analogs in the treatment of metabolic and cognitive disorders in patients with schizophrenia and other neuropsychiatric diseases. Methodology: The analysis was based on publications from PubMed and Google Scholar, using keywords related to schizophrenia, GLP-1 analogs, and metabolic disorders. Studies from 1999 to 2026 were analyzed. Results: GLP1 analogs show beneficial effects on weight reduction and improvement of glucose and lipid parameters in patients with schizophrenia. There are also indications that they may impact cognitive functions and could be used in other neuropsychiatric disorders. They have a good safety profile and do not exacerbate psychotic symptoms. Conclusion: GLP1 analogs are a promising therapeutic strategy in schizophrenia and may have broader applications in neuropsychiatric diseases; however, further clinical studies are required.